Pengaruh Kepuasan Kerja Memediasi Kompensasi Finansial Terhadap Turnover Intention: Studi Kasus Pada Karyawan Cening Bagus Oleh-oleh Khas Bali - Pustini, Ni Nyoman Ayu Trika; Hartati, Putu Sri; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Turnover intention means a person's expectation to leave his job related to dissatisfaction which results in a desire to leave his job to find another job so that employees do not have the desire to leave the company, so companies must pay attention to the factors that affect turnover intention. This research was conducted at Cening Bagus Bali Typical Souvenirs, the total sample was 42 people using a saturated sampling method technique. The tests used are test instruments, namely validity tests and reliability tests. Test the hypothesis using the path analysis test and Sobel test. The software used is SPSS for Windows. The results of the research test show that financial influence has a positive and significant effect on turnover intention, job satisfaction has a positive and significant effect on turnover intention, finance has a positive and significant effect on job satisfaction, job satisfaction cannot mediate a financial decrease in turnover intention